2008
DOI: 10.1007/s10935-007-0120-x
|View full text |Cite
|
Sign up to set email alerts
|

Practice and Physician Characteristics Associated with Influenza Vaccination Delivery Rates Following a Patient Reminder Letter Intervention

Abstract: As part of the "Provider and Patient Reminders in Ontario: Multi-strategy Prevention Tools" demonstration project, the purpose of this study was to explore the practice and physician characteristics associated with influenza vaccination rates following a reminder letter intervention for patients 65 years of age and older. Using a sample of 179 physicians, we estimated a multiple linear regression model to examine variables predictive of vaccination delivery rates. Several provider characteristics, including ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The AUC for 2013 is 72% [ 12 ]. The same nine-predictor model applied to the 2012 and 2014 datasets yielded similar confusion matrices and AUC Curves ( Figure 1 a,c) [ 5 , 6 ]. The overall trend in vaccination is shown by the three confusion matrices.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The AUC for 2013 is 72% [ 12 ]. The same nine-predictor model applied to the 2012 and 2014 datasets yielded similar confusion matrices and AUC Curves ( Figure 1 a,c) [ 5 , 6 ]. The overall trend in vaccination is shown by the three confusion matrices.…”
Section: Resultsmentioning
confidence: 95%
“…Some may not be persuadable, even with the prospect of a severe influenza season and a steady campaign of appeals to personal health, public health, and the desire to protect one’s family. Other people, conversely, will obtain a vaccination readily, with only one or two reminders from their doctor [ 5 ]. Finally, there are in-between people, those who need several reminders from various sources.…”
Section: Introductionmentioning
confidence: 99%
“…The overall objective of our study was to evaluate the effect of the P-PROMPT reminder and recall system, which applied automated and NP-augmented strategies, and pay-for-performance incentives on the delivery rates of cervical and breast cancer screening within primary care network or family health network group models in Ontario. The effect of P-PROMPT on Cervical and breast cancer screening rates | Research influenza vaccination rates has been reported earlier, 17 and its effect on the childhood immunization rates could not be determined because reliable and timely administrative data were not available.…”
Section: Points De Repère Du Rédacteurmentioning
confidence: 99%
“…The overall objective of our study was to evaluate the effect of the P-PROMPT reminder and recall system, which applied automated and NP-augmented strategies, and pay-for-performance incentives on the delivery rates of cervical and breast cancer screening within primary care network or family health network group models in Ontario. The effect of P-PROMPT on influenza vaccination rates has been reported earlier, 17 and its effect on the childhood immunization rates could not be determined because reliable and timely administrative data were not available.…”
mentioning
confidence: 98%